When less becomes more : making space for slow, simple & good - Ley, Emily (Thomas Nelson, 2019)
Statistics don<U+2019>t lie. People today are more fatigued, burned out, and overwhelmed than ever. Smartphones constantly ping and alert and demand our attention. And social media can eat up hours of our days with mindless scrolling and tapping while leaving many feeling empty and lonely. Add to that family commitments, work that is accessible around the clock, and overscheduling, and you have a life that can feel unmanageable and frantic . . . even running on empty. Emily Ley, author of bestselling Grace, Not Perfection and A Simplified Life, is here to tell you that there<U+2019>s more<U+2014>so much more. In this book, Emily Ley takes readers on a journey out of that empty place and shows them how to fill their wells with the nourishment that only true connection can provide. She also presents some radical concepts that push against the tethers of modern life, with the promise that more of the good stuff comes when we say yes to less of what keeps us empty: *Less Rush, More Rhythm *Less Liking, More Loving *Less Noise, More Calm *Less Distraction, More Connection *Less Frenzy, More Soul Rest *Less Fake, More Real *Less Fear, More Community *Less Great, More Good *Less Chasing, More Cherishing *Less Stuff, More Treasures.